Effect of jatropha seed oil meal and rubber seed oil meal as melamine urea formaldehyde adhesive extender on the bonding strength of plywood - Ong, Huei Ruey; Reddy Prasad, D. M.; Khan, Maksudur R.; Rao, D. Subba; Jeyaratnam, N.; Raman, Dinesh Kumar (Asian Network for Scientific Information, 2012)
Extenders are added to adhesive formulations to reduce resin utilization leading to cost savings. In this work, Melamine Urea Formaldehyde (MUF) resin was synthesized in the laboratory and Jatropha seed oil meal (JM) with Rubber seed oil meal (RM) were added to the Melamine Urea Formaldehyde (MUF) resin in adhesive mix formulations for interior plywood manufacturing using a laboratory press. These formulations were compared with commercialize industry wheat flour (IF). Response Surface Methodology (RSM) was used for identification of the optimum temperature and pressing time for wood adhesive performance. The experiments were conducted with temperature range from 100 to 150°C and pressing time from 50 to 250 sec. The result indicates that the effect of the extender type on plywood bonding strength was significant. The extender with high protein content has greater bonding strength performance.